Impact of chemotherapy and other prognostic factors on survival in advanced non-small cell lung cancer at Hospital Kuala Lumpur, Malaysia / Nida Sajid Ali Bangash - Ali Bangash, Nida Sajid (2017)
Determining vital prognostic factors of survival including appropriate chemotherapy regimens in patients with non-small cell lung cancer (NSCLC) is challenging due to increased prevalence and progressive nature of disease. The main objectives of this present study were to describe the prognostic factors of adult NSCLC patients via their demographic and medical data, to investigate the relationship (association and prediction) of NSCLC stage, epidermal growth factor receptor (EGFR) status and Eastern Cooperative Oncology Group (ECOG) performance status (PS) among independent variables from patients' demographic and medical data, to determine the impact of treatment groups, CT groups and lines of CT groups on survival in adult NSCLC patients, to compare survival among treatment groups, CT groups and lines of CT groups in adult NSCLC patients and to assess the impact of study predictor variables on death. This retrospective cohort study included adult (> 18 years old) NSCLC patients (n = 235) using purposive sampling method. The study was conducted in the Radiotherapy and Oncology Clinic and ward at Hospital Kuala Lumpur (HKL), Malaysia. The mean (± SD) age of adult NSCLC patients was 56.7 (±10.1) years old. Majority were males, Chinese, had adenocarcinoma, stage IV NSCLC, non-smokers with unknown EGFR status and ECOG PS score of 2. The most common site of metastasis was lung followed by bone, and most prevalent comorbidity was hypertension (HTN). Using Chi-square test, only sites of metastasis had significant association with NSCLC stage. For EGFR status, independent study variables that had significant association were age, gender, histopathology, smoking status and ECOG PS. Furthermore, ECOG PS was significantly associated with age, body weight and EGFR status. Using multinomial logistic regression analysis, the site of metastasis was the only significant predictor to NSCLC stage. Gender and histology were the significant predictors for EGFR status. The findings of binary logistic regression showed that histopathology was the only significant predictor for EGFR status. The Kaplan Meier (K-M) survival test and log-rank test suggested that for treatment groups, CT improved overall survival (OS); for CT groups, nonplatinum based (NPB) therapy showed better OS; and for lines of CT groups, only first-line tyrosine kinase inhibitors (TKIs) showed superiority for OS. The results of Cox proportional hazard (PH) regression model for treatment groups, lines of CT groups and selected study independent variables from demographic and medical data concluded that CT, RT (treatment groups), first-line TKIs, Indian (ethnicity), stage IIIA NSCLC, adenocarcinoma lung cancer (histopathology), positive-negative EGFR status and ECOG PS score of 0 and 2 were significant predictors forbetter survival, whereas PB therapy (chemotherapy groups), Malay and Chinese (ethnicity) and smokers (smoking status) were significant predictors for worse survival in locally advanced or metastatic NSCLC patients. The present study suggested the CT administered and various prognostic factors are capable of influencing survival in adult NSCLC patients.